Factors influencing the adoption of ICT'SS in extension service delivery among the extension agents in North-East, Nigeria - Mustapha, Saadu; Man, Norsida; Arif Shah, Jasmin; Kamarulzaman, Nitty Hirawaty; Tafida, Ahmadu Abubakar (University of Agriculture, Peshawar, Pakistan, 2022)
One of the strong mechanisms in the extension service delivery is the connection between agricultural research, extension and the farmers. The evolving new model of agricultural production and the small number of extension agents question old ways of providing valuable knowledge to farmers. The goal was to define the respondents’ socioeconomic characteristics, classify the types of ICT tools adopted by the respondents and identify factors influencing the adoption of ICT in extension service delivery among the respondents. Primary data were obtained using multi-stage cluster sampling technique, using organized questionnaires administered to 254 respondents. Descriptive and inferential statistics was used. The research used Rogers’ Theory of Innovation Diffusion, Rogers and Burde’s Theory of Social Change. The findings from the study have shown that GSM, radio, television, camera, internet, computer, CD/DVD player and VHS video are the most commonly used ICT components in various aspect of extension work. The multiple regression results reveal that gender, age, level of education and working experience has no significant contribution to ICT adoption while marital status, awareness, accessibility and motivation are the most influential factors influencing the adoption of ICT’s in extension service delivery. The study recommends that government for support the extension organizations with the most commonly used ICT components, ensure adequate awareness and access to ICT’s. The government support and interest will motivate the extension agents to adopt ICT’s tools and technology in extension service delivery.